TINJAUAN HUKUM PERLINDUNGAN KONSUMEN PADA TRANSAKSI ONLINE BERDASARKAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN NO. 8 TAHUN 1999 - Devonda Ananta; Findia Leona Putri Gressanda; Elen Aprilliana; Muhammad Fajar Ilham (Gapenas Publisher, 2023)
In connection with the provisions of the Consumer Protection Act No. 8 of 1999, this journal discusses the extent of consumer protection in making purchases online. Online transaction procedures are different because the internet is used as a medium and there is no need for personal interaction between the seller and the buyer. On the one hand, this is good for shoppers because there are more places to buy what they need, but on the other hand, it presents serious risks for consumers when their rights are not respected. As a consequence, customers must be legally protected while doing online transaction